Effects of Heat Treatments on Compressive Deformation Behaviors of Lattice‐Structured AlSi10Mg Alloy Fabricated by Selective Laser Melting. Issue 10 (22nd August 2019) - Suzuki, Asuka; Sekizawa, Keito; Liu, Mulin; Takata, Naoki; Kobashi, Makoto
Abstract : The effects of heat treatments on the compressive properties of a lattice‐structured AlSi10Mg alloy with a body‐centered‐cubic‐type unit cell fabricated by selective laser melting are investigated. The as‐fabricated lattice specimen fractures and does not exhibit plateau region. Fractography suggests that the crack preferentially propagates along the α‐Al/Si eutectic microstructure near the α‐Al grain boundaries in the as‐fabricated lattice specimen. The heat treatments at 300 °C for 2 h and at 530 °C for 6 h decrease the flow stress and improve the ductility. The heat‐treated lattice specimens exhibit the plateau regions with stress drops, caused by the formation of shear bands. The shear band formation of the lattice specimen heat treated at 530 °C for 6 h is more significant than that of the lattice specimen heat treated at 300 °C for 2 h. X‐ray‐computed tomography reveals that struts in the shear band are deformed locally in a bending manner. Abstract : Lattice‐structured AlSi10Mg alloy fabricated by selective laser melting and the lattice specimens heat treated at 300 and 530 °C are compressed. The as‐fabricated lattice specimen fractures in a direction of 45° from the compression axis by crack propagation along the α‐Al/Si eutectic microstructure. Heat‐treated lattice specimens deform until densified although stress fluctuates by local bending deformation.